2020
DOI: 10.2147/ccid.s190473
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sarecycline: A Review of Preclinical and Clinical Evidence</p>

Abstract: Sarecycline is a tetracycline-derived oral antibiotic, specifically designed for acne, and is approved by the Food and Drug Administration (FDA) in 2018 for the treatment of inflammatory lesions of non-nodular moderate to severe acne vulgaris (AV) in patients 9 years of age and older. It has been decades since a novel systemic antibiotic was approved to treat AV, a disease that affects up to 90% of teenagers and young adults worldwide and lasts well into adulthood. Sarecycline holds promise to yield fewer side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The FDA-approved sarecycline is used for treating acne vulgaris in patients aged nine years or above, demonstrating efficacy against moderate-to-severe, inflammatory, or non-inflammatory (comedones) forms. In addition, due to its targeted action on Cutinebacterium acnes and low blood-brain penetration, sarecycline has a good safety profile (minimal side effects), low potential to induce bacterial resistance, and also potentially low impact on the gut microbiota when compared to the broad-spectrum doxycycline and minocycline [154,155].…”
Section: Therapeutic Use Of the New Tetracyclinesmentioning
confidence: 99%
“…The FDA-approved sarecycline is used for treating acne vulgaris in patients aged nine years or above, demonstrating efficacy against moderate-to-severe, inflammatory, or non-inflammatory (comedones) forms. In addition, due to its targeted action on Cutinebacterium acnes and low blood-brain penetration, sarecycline has a good safety profile (minimal side effects), low potential to induce bacterial resistance, and also potentially low impact on the gut microbiota when compared to the broad-spectrum doxycycline and minocycline [154,155].…”
Section: Therapeutic Use Of the New Tetracyclinesmentioning
confidence: 99%
“…33 In an animal study, sarecycline showed a very low likelihood to cross the blood-brain barrier and this may explain the low rates of vestibular side effects observed in the clinical trials. [34][35][36] Although no head-to-head studies exist with other oral antibiotics, some adverse events with sarecycline seem to be lessfrequently reported than with other tetracyclines. A recently published systematic review for oral tetracycline antibiotics (sarecycline, minocycline, doxycycline, and tetracycline) in acne evaluated the efficacy and rates of adverse events for each of them.…”
Section: Narrow-and Broad-spectrum Antibioticsmentioning
confidence: 99%
“…It was approved by the FDA in 2018 for the treatment of inflammatory conditions associated with moderate to severe non-nodular acne. 66 Sarecycline has strong anti-inflammatory activity against GPB, such as Cutibacterium acnes , and has minimal anti-inflammatory activity against aerobic GNB. 67 It has a low resistance rate in tetracycline-resistant S. aureus , as well as erythromycin-resistant and clindamycin-resistant bacteria.…”
Section: Progress In Research and Development Of Drugs Against Drug-resistant Bacteriamentioning
confidence: 99%